Environmental and Agricultural Gains From Renewable Natural Gas. Issue 11 (17th May 2019) - Foxen, Robert; Fitzgerald, James
Abstract : Renewable natural gas (RNG), also known as biomethane, is produced by "purification" of biogas generated by the anaerobic decomposition of organic material. The difference between renewable natural gas (RNG) and fossil natural gas is the source of methane. Fossil natural gas is produced over millions of years by decay of organic matter in underground deposits, while RNG is a by‐product of anaerobic digestion of organic wastes generated from various human, industrial, or agricultural activities. Feedstocks for RNG include municipal waste water, landfill deposits, digestion of manure from dairies and hog farms, and digestion of food wastes, to name a few. Like fossil natural gas, RNG can be used to power trucks, buses, and cars, or to power electric generation. It is estimated that RNG could displace 16–25 percent of all the diesel fuel currently used in the United States.